Promoting H2O2 production via 2-electron oxygen reduction by coordinating partially oxidized Pd with defect carbon - Qiaowan Chang (Nature Portfolio, 2020)
Electrocatalysts which deliver high selectivity for two-electron oxygen reduction to hydrogen peroxide in acidic media are sought to replace the conventional anthraquinone process. Here, the authors develop partially oxidised palladium clusters on carbon nanotubes with near 100% selectivity.